Toward a picture of Chahar Mahal va Bakhtiari Province, Iran, as a linguistic area. Issue 2 (17th October 2021) - Anonby, Erik; Taheri-Ardali, Mortaza; Stone, Adam
Abstract: Language documentation has been carried out in Iran since the late 1800s but in a sporadic way, and even now, the scholarly picture of the country's linguistic landscape is fragmentary. The present article responds to this state of affairs in a modest way by working toward a systematic overview of the language situation in one area of the country: Chahar Mahal va Bakhtiari Province of western Iran, where the high Zagros Mountains open onto the Iranian Plateau. In this study, conducted in the context of the Atlas of the Languages of Iran (ALI) research programme, we chronicle our research process for this region, beginning with an inventory of languages spoken here—varieties of Bakhtiari, Charmahali, and Turkic—and an overview of their geographical distribution. This initial step enabled us to select 30 varieties from 26 locations across the province for in-depth research, including implementation of the ALI language data questionnaire. Data generated by the study have resulted in two language distribution maps as well as a series of linguistic structure maps. Initial analysis of lexical and phonological data provides insight into defining features of each language as well as structures shared between them as a result of language contact in the region.